Overview of optic neuritis and visual outcome in a tertiary care hospital of central Nepal - Dahal, Polina; Bastola, Pradeep (Journal of Chitwan Medical College, 2021)
Background: Optic neuritis is a visually debilitating and usually painful condition of the eye. As per the Optic neuritis treatment trial (ONTT) intravenous methylprednisolone has shown to accelerate recovery in Optic neuritis and has also been proven to somewhat decrease recurrence. This study was aimed to provide demographics of patients, clinical findings and features, investigative findings in cases of optic neuritis and the outcome of treatment for future references. Methods: This prospective observational study was carried out in Chitwan Medical College, Department of Ophthalmology from 16 August 2021 to 15 October, 2021. Newly diagnosed cases of Optic neuritis were included in the study for treatment with intravenous methylprednisolone and oral steroids. SPSS version 26 was used to analyze the data entered in a specified proforma. Results: Fourteen 63.6% of the study participants were females. Mean age of presentation of the study subjects was 51.45 years (Range 33-78, +- 13.0). Commonest presenting complaint was sudden onset diminution of vision (100%). Radiographic findings were present in 36.3 %. All study subjects had varying grades of relative afferent pupillary defect (RAPD), 45.4% participants had color vision defect, and visual field changes were detected in 36.6% (8) study subjects. Conclusions: Optic neuritis presents with sudden onset diminution of vision usually in one eye. The treatment outcome with IV steroids followed by oral steroids when initiated early in cases of optic neuritis have an excellent visual outcome.